2019
DOI: 10.1002/adem.201900169
|View full text |Cite
|
Sign up to set email alerts
|

Corona Poling Conditions for Barium Titanate/Epoxy Composites and their Unsteady Wind Energy Harvesting Potential

Abstract: The objective of this paper is to design and fabricate barium titanate (BTO)/epoxy composites, investigate the effect of poling conditions on their piezoelectric properties, and obtain their unsteady energy harvesting potential. The poling condition test deals with the effect of the poling conditions on the piezoelectricity of BTO/epoxy composites. The specimens are polarized by corona poling under different conditions, and their piezoelectric coefficient d33 is measured. The distribution of the piezoelectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…All of the above-mentioned studies have focused on composite materials in which continuous Fe-Co fibers are embedded in the epoxy or aluminum alloy matrix. However, the flexibility of these composites is not good enough to meet the requirement of wearable applications, hence, it is necessary to develop a lighter and more flexible composite material [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…All of the above-mentioned studies have focused on composite materials in which continuous Fe-Co fibers are embedded in the epoxy or aluminum alloy matrix. However, the flexibility of these composites is not good enough to meet the requirement of wearable applications, hence, it is necessary to develop a lighter and more flexible composite material [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the poling temperatures were 75 °C for KNN nanoparticles/epoxy and 65 °C for BTO nanoparticles/epoxy, respectively. (13,14) Poling was performed along the thickness direction, and Au electrodes were coated on the upper and lower surfaces using a sputtering machine (SC-701 Mk II, Sanyu Electron Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…The first approach is to use lead-free piezoceramics such as BTO and potassium sodium niobate (KNN). (13,14) These piezoceramics also have a perovskite structure and show relatively large piezoelectric constants. They have widely been considered as the main alternative piezoceramics to lead-based ones.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism differs from the piezoelectric material. That is, the output voltage of the piezoelectric material is proportional to the electric field amplitude associated with the stress amplitude [3].…”
Section: Theorymentioning
confidence: 99%
“…Piezoelectric materials have been considered as wearable energy harvesting devices [2,3], and mainly integrated into shoes to harvest a large amount of mechanical energy [4,5,6,7,8,9]. For example, Turkman et al have reported 1.4 mW of generated power by the applied mass of 90 kg [9].…”
Section: Introductionmentioning
confidence: 99%